EFEKTIVITAS HERBISIDA NABATI EKSTRAK DAUN KETAPANG (Terminalia catappa L.) TERHADAP GULMA Asystasia gangetica L. - Putri Ramadhani; Saripah Ulpah (DINAMIKA PERTANIAN, 2022)
Asystasia gangetica is considered one of the invasive weeds and is often found in residential areas and is one of the most important weeds to plant. The aim of the study was to evaluate the effectiveness of the interaction between extract concentration and leaf condition of Terminalia catappa L. extracted from Asystasia gangetica. The study was conducted using a completely randomized design using two factors. The first factor was the condition of the extracted leaves, which were fresh, newly fallen and dried leaves. The second factor was the extract concentrations, which were 50, 75 and 100%. The parameters were the time of germination, the height of the plant, the number of leaves, the length of the root and the weight of the grass. The results of the experiment showed that there was an interaction between the extract concentration and the state of the extracted Terminalia catappa Leaf with all the observed parameters. In general, growth retardation increased with increasing extract concentration. Fungicidal potency was shown by the extract obtained from fresh leaves, followed by the extract from newly fallen leaves and the least from dried leaves.